DETERMINATION OF OIL EXTRACTION RATE FROM Spirulina sp. AND Chlorella sp. BY USING CELL DISRUPTION TECHNIQUE - Susiana Melanie; Diini Fithriani (Widyariset, 2015)
Oil derived from microalga has a big potential to substitute fossil fuel so that the oil extraction method needs to be developed. This study aims to compare the method for cell disruption in oil extraction of Spirulina sp. and Chlorella sp. microalgae. Spirulina sp. and Chlorella sp. were cultivated each in a pond with maximum capacity of 600 liters at Biotechnology Laboratory of Research and Development Center for Marine and Fisheries Product Processing and Biotechnology. Spirulina sp. were harvested by filtered it using satin. Chlorella sp. was harvested using coagulant NaOH, so it was needed to be neutralized to pH 7 with citric acid addition. The cell wall of Spirulina sp. and Chlorella sp. then was ruptured using sonicator and microwave, while other sample without disruption as control. The suspension then was macerated with n-hexane solvent, to extract the oil content. Oil content of Spirulina sp. which has been collected from this experiment gave result control: microwave: sonicator as 1.17%, 1.28%, and 1.97% respectively. Meanwhile, oil content of Chlorella sp. gave result from control, microwave, and sonicator as 0.93%, 1.20%, and 1.69% respectively. It was concluded that sonicator is the best method in oil extraction of cultured microalgae.